A Critical Success Factors Framework for the Improved Delivery of Social Infrastructure Projects in South Africa - Alfred R. Rasebotsa; Justus N. Agumba; Oluseyi J. Adebowale; David J. Edwards; John Posillico (Buildings)
Social infrastructure projects (SIPs) play a critical role in fostering social and economic development in the public sector. However, SIPs often face significant challenges, partly due to a lack of research on critical success factors (CSFs) specific to these projects. Despite the importance of SIPs, scant research focuses upon enhancing SIPs’ performance. Consequently, a CSF framework is developed for improving the delivery of SIPs in South Africa. Through a quantitative survey of 124 construction professionals, the study identified key factors essential for successful SIPs delivery. Data were analysed using descriptive and inferential statistics, revealing a significant consensus among infrastructure stakeholders on CSFs needed for successful SIP delivery. Constituent elements of the framework integrate CSFs related to clients, contractors, projects and project management factors; external factors were excluded from the framework due to a lack of supporting evidence. The study offers a practical understanding for infrastructure stakeholders in South Africa to: overcome the challenges that hinder SIPs’ performance; and enhance the SIP delivery processes. Cumulatively, these palpable deliverables contribute to the nation’s social and economic development objectives. While the research is focused on South Africa, the CSFs framework could inform SIP delivery strategies in similar socio-economic and institutional contexts globally. The study reveals that SIP success depends on the identified factors and offers a structured framework for improving project outcomes. The framework highlights CSFs, including effective monitoring and timely decision-making for clients; subcontractor coordination and quality assurance for contractors; economic stability and advanced technology for projects; and team collaboration and expertise utilisation for project management. This systematic approach could enhance effective planning, execution and evaluation of SIPs, leading to more efficient delivery. However, the study’s focus on the Mpumalanga and Limpopo provinces limits the generalisability of the findings to other regions with different socio-economic and environmental conditions. Therefore, future research could explore the applicability of this framework in diverse social, political, and geographical contexts.